Long-Term Effects of Low-Dose Chlorpyrifos Exposure on Serum Albumin Levels in Male Wistar Rats - Wisudanti, Desie Dwi; Hidayat, Noval; Jauhani, Muhammad Afiful (Journal of Biomedicine and Translational Research, 2024)
Background: Chlorpyrifos is one of the organophosphate pesticide types frequently utilized as a pest control agent in Indonesia. Despite its effectiveness in combating pests, the residue levels of chlorpyrifos in the environment and plants have raised serious concerns. Long-term accumulation of chlorpyrifos in the body can lead to organ damage, particularly in the liver and kidneys, which may decrease serum albumin levels.Objective: To investigate the impact of low-dose chlorpyrifos exposure over time on serum albumin levels in Wistar rats.Methods: Thirty male Wistar rats were divided into five groups: the normal control group (Kn) received normal saline solution (+5% Tween 20) orally for 56 days, while the treatment groups (K1, K2, K3, and K4) were administered chlorpyrifos at a dose of 5 mg/kg body weight for 7 days (acute), 14 days (subacute), 28 days (subchronic), and 56 days (subchronic) orally. Serum albumin levels were measured using the dye-binding method with a spectrophotometer.Results: The measurement results indicate that the normal control group (Kn) had the highest serum albumin levels (4.326±0.519 g/dL). Serum albumin levels decreased in the groups treated with chlorpyrifos. The longer the chlorpyrifos exposure, the lower the serum albumin levels. The lowest serum albumin levels were found in group K4 with chlorpyrifos exposure for 56 days (2.826±0.358 g/dL). Statistical analysis using One-way ANOVA and Post Hoc LSD tests showed significant differences (p<0.05) between all treatment groups (K1, K2, K3, and K4) and the control group (Kn).Conclusion: This study shows that administering low-dose chlorpyrifos over a period of 7 to 56 days has a significant effect in reducing serum albumin levels in Wistar rats. The clinical implications of this decrease in serum albumin levels need to be considered in the context of exposure to organophosphate pesticide residues in humans.